Śrāddhamayūkhaḥ prārabhyate - Nīlakaṇṭha, 17th cent (Neṭīva Opiniyana Yantrālaye, 1897)
On Śraddha Hindu rite; portion of Bhagavantabhāskara, classical digest of Hindu rituals of Nīlakaṇṭha, 17th cent.